2019
DOI: 10.1111/and.13357
|View full text |Cite
|
Sign up to set email alerts
|

Can haematologic parameters be used to predict testicular viability in testicular torsion?

Abstract: Funding informationThe Beijing hospital authority "dengfeng" talent training plan (DFL20151102); The Beijing hospital authority "yangfan plan": pediatric urology (ZYLX201709). AbstractThe purpose of this study was to evaluate the predictive value of haematologic parameters for testicular survival in torsion. Children with testicular torsion (TT) treated in Beijing Children's Hospital from January 2006 to December 2018 were enrolled in this study. Patient data collected in this study included age, symptom durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 16 publications
(18 reference statements)
1
20
0
Order By: Relevance
“…Our previous studies have found that MPV could be used to predict the testicular salvage rate during the window phase (8–51 hr). After our follow‐ups, we were surprised to find that MPV might predict testicular atrophy after surgery; the cut‐off value was 9.9 fl (He, Zhang, & Sun, ). Although this group of patients showed positive results, we still have reservations about whether MPV can really predict long‐term prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have found that MPV could be used to predict the testicular salvage rate during the window phase (8–51 hr). After our follow‐ups, we were surprised to find that MPV might predict testicular atrophy after surgery; the cut‐off value was 9.9 fl (He, Zhang, & Sun, ). Although this group of patients showed positive results, we still have reservations about whether MPV can really predict long‐term prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…9 10 Several studies confirmed that there is a relationship between testicular torsion, defined as an acute vascular disease, and platelet activation which results in higher mean platelet volume (MPV). [11][12][13] Therefore, platelet volume indices (PVIs) can be introduced as potential markers of early diagnosis of testicular torsion.…”
Section: Key Messagesmentioning
confidence: 99%
“…There are studies reporting that there is a relationship between haematological parameters and testicular recovery rate (He, Zhang, & Sun, 2019; Peretti et al, 2019; Jang et al, 2019). He et al.…”
Section: Discussionmentioning
confidence: 99%
“…He et al. (2019) reported that there was a relationship between MPV, symptom duration and degree of spermatic cord torsion and viability of the testicle. Peretti et al (2019) reported that MPV was a parameter showing testicle viability in TT patients presenting in less than 6 hr of symptom duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation